Management of insulin pump therapy in children with type 1 diabetes. Issue 6 (14th August 2014) - Abdullah, Nadeem; Pesterfield, Claire; Elleri, Daniela; Dunger, David B
Abstract : Insulin pump therapy is a current treatment option for children and adolescents with type 1 diabetes. Insulin pumps can provide a greater flexibility in insulin administration and meal planning, as compared with multiple insulin injections, and they may be particularly suitable for the paediatric age group. Many young people with diabetes have integrated insulin pumps into their daily practice. The use of insulin pumps can also be supplemented by the information retrieved from continuous glucose monitoring in the sensor-augmented pump therapy, which may improve glycaemic control. In this review, we describe the principles of pump therapy and summarise features of commercially available insulin pumps, with focus on practical management and the advantages and disadvantages of this technology.